The Epidemiology and Global Burden of Atopic Dermatitis: A Narrative Review - Ab. Hadi, Hazrina; Tarmizi, Aine Inani; Khalid, Kamarul Ariffin; Mario, Gajdacs; Aslam, Adeel; Jamshed, Shazia (MDPI, 2021)
The global epidemiology of atopic dermatitis (AD) in the current decade (2009–2019) has not been extensively reported. Epidemiological studies play an important role in presenting the risk factors of AD, as detailed prevalence and incidence data could demonstrate the burden of disease in the population of adults, adolescents, and children in different geographical regions. Thus, the primary objective of this review was to assess and summarize the epidemiological studies of the prevalence and incidence of AD in different age groups, focusing on data from studies published for 2009 to 2019. After a thorough literature search, six countries were identified from African, Asian, and European regions respectively, who published studies on AD. In contrast, only two studies were identified from Australia and New Zealand, three countries from North America and two from South America published AD studies, respectively. The highest prevalence of AD from included studies was noted among Swedish children with 34%, while the lowest prevalence was in Tunisian children with 0.65%; studies reporting incidence data were far less numerous. A common trend in the prevalence of AD was that children would have a higher prevalence as compared to adolescents and adults. The severity and morbidity of the disease showed variance with age, sex, socioeconomic characteristics, geographical location, and ethnicity. Environmental factors played an important role as causative agents in AD. The risk factors that were proven to cause and induce AD were skin barrier impairments due to FLG mutation, changes in the environment, and diet. FLG mutation may impair the skin barrier function by disruption of pH and hydration maintenance of the skin. Lastly, there were only a few studies on the incidence of AD in the 21st century. Therefore, epidemiological studies on childhood and adulthood AD in different continents are still needed, especially on the incidence of AD during adulthood.